2018
DOI: 10.1039/c8ra06824k
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungus Pseudofusicoccum stromaticum produces cyclopeptides and plant-related bioactive rotenoids

Abstract: Pseudofusicoccum stromaticum produces cyclopeptides and plant-related rotenoids, which are responsible for its antiproliferative effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The two rotenoids rotenolone and tephrosin (Figure 1), previously reported in plants belonging to the genera Derris and Tephrosia, were found to be produced by the endophytic fungus Pseudofusicoccum stromaticum isolated from the timber tree Myracrodruon urundeuva [79]. In plants, rotenoids are formed from flavonoids in a multi-step pathway where chalcone isomerase (CHI) and CHS play a role as key enzymes [98].…”
Section: Rotenoids: Rotenolone and Tephrosinmentioning
confidence: 86%
See 1 more Smart Citation
“…The two rotenoids rotenolone and tephrosin (Figure 1), previously reported in plants belonging to the genera Derris and Tephrosia, were found to be produced by the endophytic fungus Pseudofusicoccum stromaticum isolated from the timber tree Myracrodruon urundeuva [79]. In plants, rotenoids are formed from flavonoids in a multi-step pathway where chalcone isomerase (CHI) and CHS play a role as key enzymes [98].…”
Section: Rotenoids: Rotenolone and Tephrosinmentioning
confidence: 86%
“…During the investigation of the P. stromaticum genome, the gene encoding for a CHI-like protein was identified, elucidating the ability of this fungus to produce plant-related rotenoids, while no CHS homologue could be found. Protein alignment analysis and maximum likelihood phylogenetic reconstruction analysis have revealed that fungal CHI-like enzymes have more than one substrate specificities since they recognize chalconoids other than (2S)-naringenin [79].…”
Section: Rotenoids: Rotenolone and Tephrosinmentioning
confidence: 99%
“…New coumarins showing antifungal and anticholinesterase activity were isolated [10]. In another study, eleven compounds were identified and one compound, tephrosin, showed activity against a colorectal cancer cell line (HCT-116) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Almost twenty years ago, Gensheimer and Musheigan discovered that the CHIdomain-containing protein family extends into fungi, slime molds, and γ-proteobacteria (8). Previous studies mention the presence of a fungal CHI-domain-containing protein family (6,(9)(10)(11)(12)(13) and speculate whether these proteins have CHI activity; however, to date, no functional characterization of the fungal CHI-domain-containing proteins has been reported.…”
Section: Introductionmentioning
confidence: 99%